Malignant Solitary Fibrous Tumor of the Pleura - Aydın, Sıyamı; Çakmak, Muharrem; Ak, Sema; Calik, Ilknur (My University, 2022)
The malignant solitary fibrous tumor of the pleura is a spindle cell mesenchymal tumor originating from fibroblasts. It is a very rare tumor. It develops from mesenchymal cells of the submesothelial tissue of the visceral pleura. Malignant solitary fibrous tumors originating from the parietal pleura are even more rare. In this study, we aimed to share a patient with malignant mesenchymal fibrous tumor originating from the parietal pleura and invading the rib.
Keywords: Adli Tıp